Gastrodin From Gastrodia elata Enhances Cognitive Function and Neuroprotection of AD Mice via the Regulation of Gut Microbiota Composition and Inhibition of Neuron Inflammation - Fasina, Opeyemi B.; Wang, Jianyu; Mo, Jianxia; Osada, Hiroyuki; Ohno, Hiroshi; Pan, Wensheng; Xiang, Lan; Qi, Jianhua (Frontiers in Pharmacology, 2022)
Gastrodin (Gas) is known to exhibit neuroprotective effects in Alzheimer’s disease (AD). However, the detailed mechanism of action is still unclear. In the present study, we focused on the microbiome–gut–brain axis to investigate the mechanism of action of Gas using a D-galactose (Dgal)-induced AD model. Gas reversed the memory dysfunction of Dgal-administrated mice. Neurons in the cerebral cortex and hippocampus were reduced in the Dgal-administrated group and the decrease of the neurons was suppressed in 90 and 210 mg/kg Gas treatment groups. 16S rRNA sequence analysis was carried out to explore the composition of gut microbiota in fecal samples of mice. Gas treatment had a positive correlation with Firmicutes and had a negative correlation with Cyanobacteria, Proteobacteria, and Deferribacters. Importantly, the LPS and proinflammatory cytokines in brain increased in Dgal administrated mice, but these parameters recovered to normal levels after oral administration of Gas. To determine whether the microbiota–gut–brain axis is involved in the neuroprotective effect of Gas, the mice were given antibiotic cocktail before and during the trial period to decrease the gut microbiota of mice. The antibiotic cocktail partially eliminated the neuroprotective effect of Gas by changing the gut microbiome composition. These results indicated that Gas improves the memory of AD mouse model via partly targeting the microbiota–gut–brain axis and mitigating neuron inflammation.